PENGARUH KEADILAN PROSEDURAL DAN KEADILAN DISTRIBUTIF TERHADAP KOMITMEN AFEKTIF KARYAWAN BAGIAN PRODUKSI DI PT. X - ABIWORO, RISANG (Jurnal Ilmu Manajemen (JIM), 2016)
This study aims to determine the impact of procedural justice and distributive justice on commitment affective in the production employees at PT. X. This type of research is quantitative. The sampling technique is used Slovin theory, portion of production is to sample 118 respondents. The statistical analysis used in this research is by using SPSS. The scale of measurement in this study using a Likert scale. Analyzed with multiple regression tecnique, the result shows that procedural justice and distributive justice can be used to predict the commitment affective (F : 41.898.,Sig :000). Conclusion of this research show that procedural justice and distributive justice the significant effect on affective commitment in the production employees at PT. X eitherpartially or simultaneous. Keywords :Procedural justice, Distributive justice, Affective commitment